The Influence of Self-Confidence on Students’ Mathematical Reasoning Ability at SMA Negeri 3 Purwokerto - Tobingatus Salimah; Sofiana Mardiyantiningsih (International Journal of Research in Mathematics Education, 2025)
Mathematical reasoning is a fundamental skill that students need develop in the process of learning mathematics. This skill is crucial, as one of the primary objectives of mathematics education is to enable students to apply reasoning in understanding mathematical forms and properties, perform mathematical manipulations to develop generalizations, construct factual knowledge, and articulate mathematical arguments and statements. Among the various factors that may influence students' mathematical reasoning ability, one of them is self-confidence. Students with a high level of self-confidence tend to exert greater effort in problem-solving, demonstrate persistence in overcoming difficulties, and are less likely to give up when faced with challenges in mathematics. This study aims to analyze and describe the influence of self-confidence on the mathematical reasoning ability of students at SMA Negeri 3 Purwokerto. The research employed a quantitative approach using a survey method. The study was conducted at SMA Negeri 3 Purwokerto with a population comprising 396 eleventh-grade students. The sample was selected through simple random sampling, using Slovin's formula, which resulted in a total sample of 199 students. Data were collected using two instruments: a questionnaire to measure the self-confidence variable and a test to assess students’ mathematical reasoning abilities. The findings indicate that self-confidence significantly influences students' mathematical reasoning ability. The degree of influence is reflected in the coefficient of determination (R²) value of 0.203, indicating that self-confidence accounts for 20.3% of the variance in students’ mathematical reasoning ability. The remaining 79.7% is attributed to other factors not examined in this study. These results highlight the importance of fostering self-confidence in students as part of efforts to improve their mathematical reasoning skills.